"PALYNOMORPH ASSEMBLAGE OF THE CHENQUE FORMATION, LATE OLIGOCENE?-MIOCENE FROM GOLFO SAN JORGE BASIN, PATAGONIA, ARGENTINA. PART 3. POLYCOLPATE AND TRICOLPORATE POLLEN" (Ameghiniana, 2014)
Systematic descriptions of 19 angiosperm pollen species from the late Oligocene?-Miocene Chenque Formation, golfo San Jorge basin are presented in this third part; the following 4 new species are proposed: Dryadopollis minima, Poluspissusites puntensis, Senipites patagonica and Margocolporites tenuireticulatus. A new combination, "Rhoipites" cienaguensis (Dueñas) combo nov., is proposed and a revised description of Rhoipites romeroi Baldoni is given. The following species are also described for the first time from Argentina: "Rhoipites" cienaguensis (Dueñas) Barreda comb nov., Cupanieidites reticularis Cookson and Pike, Margocolporites vanwijhei Germeraad, Hopping and Müller and Psilatricolporites operculatus Van der Harnmen and Wijmstra.